A scoping review and critical evaluation of the methodological quality of clinical practice guidelines on nutrition in the preconception - Ancira-Moreno, Mónica; Burrola-Méndez, Soraya; Muñoz-Manrique, Cinthya; Omaña-Guzmán, Isabel; Hoyos-Loya, Elizabeth; Trejo-Domínguez, Alejandra; Hernández-Cordero, Sonia; Mazariegos, Mónica; Smith, Natalia; Tavano-Colaizzi, Loredana; Mier-Cabrera, Jennifer; Avendaño-Álvarez, Fermín; et al. (Frontiers in Nutrition, 2023)
Clinical practice guidelines (CPGs) contain recommendations for specific clinical circumstances, including maternal malnutrition. This study aimed to identify the CPGs that provide recommendations for preventing, diagnosing, and treating women's malnutrition. Additionally, we sought to assess the methodological quality using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. An online search for CPGs was performed, looking for those that contained lifestyle and nutritional recommendations to prevent, diagnose and treat malnutrition in women during the preconception period using PubMed and different websites. The reviewers utilized the AGREE II instrument to appraise the quality of the CPGs. We defined high-quality guidelines with a final score of>70%. Our analysis included 20 CPGs. The overall quality assessment of CPGs was 73%, and only 55% reached a high-quality classification. The domains in the guidelines classified as high-quality had the highest scores in "Scope and Purpose" and "Clarity of Presentation" This is a provisional file, not the final typeset article with a median of 98.5% and 93%, respectively. Further assessment is needed to improve the quality of the guidelines, which is an opportunity to strengthen them, especially in the domains with the lowest scores.